2018
DOI: 10.1590/1678-5150-pvb-5371
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da associação dupla dose PGF2 alfa-eCG no proestro de vacas leiteiras mestiças submetidas à IATF

Abstract: RESUMO: Objetivou-se avaliar o efeito de uma ou duas doses de prostaglandina F2α (PGF2α) associada ou não a gonadotrofina coriônica equina (eCG) sobre a dinâmica folicular, a função luteal pré-ovulatória, assim como as características morfofuncionais pós-ovulatórias do corpo lúteo (CL) em fêmeas mestiças cíclicas submetidas a um protocolo de inseminação artificial em tempo fixo (IATF). Para tanto, 29 vacas 3/4 Gir x Holandês multíparas foram submetidas ao exame de ultrassonografia (US) transretal e após a dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…According to Rahe et al (1980), low LH pulsatility can be observed when plasma P4 concentrations are high, from 5 to 8ng/mL. Therefore, the high circulating P4 concentrations at the time of ovulation synchronization observed in the animals of the High-P4 group are close to the values found for pregnant cows (10.45ng/mL) (Rodrigues et al 2018), and this hormonal scenario prevents follicular maturation and, consequently, ovulation from occurring. When cows are in a hormonal environment with high preovulatory circulating P4 concentrations, a negative feedback occurs in the secretion of GnRH by the hypothalamus, as well as decreased LH pulsatility, and this condition is determining for the development of smaller diameter follicles (Dias et al 2009).…”
Section: Discussionmentioning
confidence: 72%
“…According to Rahe et al (1980), low LH pulsatility can be observed when plasma P4 concentrations are high, from 5 to 8ng/mL. Therefore, the high circulating P4 concentrations at the time of ovulation synchronization observed in the animals of the High-P4 group are close to the values found for pregnant cows (10.45ng/mL) (Rodrigues et al 2018), and this hormonal scenario prevents follicular maturation and, consequently, ovulation from occurring. When cows are in a hormonal environment with high preovulatory circulating P4 concentrations, a negative feedback occurs in the secretion of GnRH by the hypothalamus, as well as decreased LH pulsatility, and this condition is determining for the development of smaller diameter follicles (Dias et al 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Com isso, várias estratégias estão sendo desenvolvidas para manipular as taxas de concepção em vacas de corte e leite. Utilização de progesterona exógena após a inseminação artificial (IA) (Moreira et al, 2020;Pugliesi et al, 2016), bem como a utilização de dose adicional de prostaglandina F2alfa (Ferreira et al, 2020;Rodrigues et al, 2018), além de componentes vitamínicos, minerais e outros hormônios (Bonato et al, 2021;Lima et al, 2017;Peixoto et al, 2021;Souza et al, 2014).…”
Section: Introductionunclassified